Acidic Microenvironment Enhances Cisplatin Resistance in Bladder Cancer via Bcl-2 and XIAP - Kaede Hiruma; Vladimir Bilim; Akira Kazama; Yuko Shirono; Masaki Murata; Yoshihiko Tomita (Current Issues in Molecular Biology)
Cisplatin (CDDP) remains a key drug for patients with advanced bladder cancer (BC), despite the emergence of new therapeutic agents; thus, the identification of factors contributing to CDDP treatment resistance is crucial. As acidity of the tumor microenvironment has been reported to be associated with treatment resistance and poor prognosis across various cancer types, our objectives in this study were to investigate the effects of an acidic environment on BC cells and elucidate the mechanisms behind CDDP resistance. Our findings show that BC cells cultured under acidic conditions developed cisplatin resistance as acidity increased. Notably, CDDP administered to BC cells in a pH 6.0 environment required double the concentration, compared to those in a pH 7.5 environment, to achieve equivalent toxicity. Using chloroquine and navitoclax, we identified the involvement of the Bcl-2 and LC3B pathways in the acquisition of CDDP resistance under acidic conditions. A Western blot analysis revealed that the activations of Bcl-2 and XIAP expression appear to inhibit both apoptotic and autophagic cell death. Taken together, these results suggest that alleviating the acidity of the tumor microenvironment in clinical settings might enhance BC sensitivity to CDDP.